1999
DOI: 10.1161/01.res.85.7.606
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Ca 2+ Homeostasis by Atypical Na + Currents in Cultured Human Coronary Myocytes

Abstract: Primary cultured human coronary myocytes (HCMs) derived from ischemic human hearts express an atypical voltage-gated tetrodotoxin (TTX)-sensitive sodium current (I(Na)). The whole-cell patch-clamp technique was used to study the properties of I(Na) in HCMs. The variations of intracellular calcium ([Ca2+]i) and sodium ([Na+]i) were monitored in non-voltage-clamped cells loaded with Fura-2 or benzofuran isophthalate, respectively, using microspectrofluorimetry. The activation and steady-state inactivation proper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
40
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(47 citation statements)
references
References 24 publications
7
40
0
Order By: Relevance
“…The present study demonstrates the biophysical and molecular characteristics of I Na in cultured hASMCs, consistent with the previous reports in human cultured myocytes (3,17,23,25). We also demonstrate that the expression of SCN9A is limited to cultured and diseased conditions in human and rabbit aorta smooth muscle cells and is absent in isolated native aorta.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The present study demonstrates the biophysical and molecular characteristics of I Na in cultured hASMCs, consistent with the previous reports in human cultured myocytes (3,17,23,25). We also demonstrate that the expression of SCN9A is limited to cultured and diseased conditions in human and rabbit aorta smooth muscle cells and is absent in isolated native aorta.…”
Section: Discussionsupporting
confidence: 92%
“…After being cleaned of connective tissue and adhered fat tissue, isolated arteries were cut open longitudinally and the endothelium was removed by gently rubbing with a cotton swab. The aorta was cut into small pieces about 1-3 mm 3 and then incubated in a gently shaking bath at 37°C in Ca 2ϩ -free Tyrode solution containing 0.4 mg/ml collagenase type IA (Sigma) for 90 min. The isolated cells were then used for later experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The inward I Na we observed in human PASMC possessed biophysical and pharmacological characteristics similar to those previously identified in other human VSMC [4,5,7,16,28]: sensitivity to TTX (EC 50 17.5 nM), -60 to -50 mV activation threshold, -15 to 0 mV peak amplitude potential, -70 to -65 mV half-inactivation voltage, -25 to -15 mV half-activation voltage, and activation (τ act ∼1 ms) and inactivation time (τ inact ≤ 4 ms) constants. Similarities in the window currents, -60 to -10 mV in 3human PASMC and other VSMC [4,7], also suggest that Na + channels are active over a wide range of physiological E m , and that they may contribute to the regulation of resting E m in human PASMC. However, in unpublished observations, we found that TTX did not significantly alter human PASMC E m (-41.2±2.6 mV, -46.2±3.1 mVin TTX, n=4, data not shown) indicating that Na + channel activity does not modulate E m in cultured normal human PASMC.…”
supporting
confidence: 82%
“…Measurement of Intracellular Ca 2ϩ -Intracellular Ca 2ϩ level was measured in single cells, as previously described (21). Briefly, the dual excitation ratiometric Ca 2ϩ -sensitive dye, Fura-2, was used for [Ca 2ϩ ] i imaging measurements by means of an Olympus-LSR system (MER-LIN; Life Science Resources Ltd., Cambridge, UK).…”
Section: Methodsmentioning
confidence: 99%